Safety in the chemistry and biochemistry laboratory - Picot, Andre (VCH, 1995)
This includes adequate knowledge concerning dangerous substances and intermediates that may be formed and which can determine the stability and toxicity of mixtures; the risks inherent to certain reactions and manipulations,...